Choices and options in the care procurement process of bundled payment contracts: A literature-based overview from a payer’s perspective - Sander Steenhuis; Jeroen van der Wolk; Eric van der Hijden (PLoS ONE, 2026)
Context While the potential of bundled payment models to facilitate value-based care is hard to overestimate, the complexity of designing an effective and feasible care procurement contract forms a formidable barrier to their use. The objective of this study is to identify, structure, and interpret the key design choices and options during the care procurement process of bundled payment contracts using a payer’s perspective. Methods Two reviewers independently conducted an iterative qualitative content analysis of a selectively sampled set of articles from a prior scoping review. First, they extracted and clustered all text excerpts about design choices or options relevant to a bundled payment procurement process. Where available, they assessed the potential impact of choosing that option. Second, the choices and options were analytically organized into six phases of a care procurement process. Third, the resulting framework was evaluated in an external expert panel session. Findings 33 design choices with 110 unique options were identified and structured within a framework. An example of a design choice is to ‘determine the method to select care and cost to include in the bundle,’ in which case 4 options were identified: 1. based on historic claims data, 2. based on best-practices and/or local care pathways, 3. based on evidence-based clinical guidelines, and 4. based on the provider type or specialism that is willing to collaborate. Conclusions This study helps understand how design choices for payers to purchase value-based care with bundled payment contracts are context-dependent (e.g., in a single-payer system options are different than in a multi-payer system), interchangeable (i.e., different choices can achieve similar effects) and/or interrelated (i.e., choosing one option can have a positive or negative impact on the options in other procurement phases). The framework assists payers (and providers) in developing an effective and feasible bundled payment contract.